The relationship between food security and functional foods - Valieva G.R. (BIO Web of Conferences)
During the last ten years, a great interest of the scientific community lies in the study of functional foods and their importance in addressing the challenges of food security. Functional foods include ingredients or dishes that have specific properties that favorably affect health and reduce the risks of various kinds of diseases. The relevance of this study lies in the ever-increasing focus on healthy living, which is achieved through the consumption of functional foods in the world. Recent studies suggest that the food market is increasing functional foods, which play a key role in shaping consumer preferences and healthy eating habits. The importance of the study is to provide evidence-based recommendations for the production and intake of these products, which are a key component in improving health outcomes. The role of functional foods have certain properties that have a positive impact on health and prevention of various kinds of diseases, are one of the main tools in the strategy to improve food security. The production and consumption of this type of product is an important component of sustainable development of the food system.